Pelaksanaan Program Gerakan Masyarakat Lisu Massikola Paimeng (Gemar Limas) di Kabupaten Bone - Andi Reza Zulkarnain; Rahmatullah; Ashar Prawitno (Departemen Ilmu Pemerintahan Fisip Unhas, 2025)
In Bone Regency, the ability of villages to report data on out-of-school children into the data collection system remains a significant challenge. The collaborative issues that emerged among stakeholders in the implementation of the Gemar Limas (Gerakan Masyarakat Lisu Massikola Paimeng) Program in Bone Regency indicate inefficiencies and ineffectiveness in coordination and communication. This study aims to analyze the collaborative governance involving the Regional Development Planning Agency (Bappeda), the Department of Education, the Department of Women's Empowerment and Child Protection, Community Learning Activity Centers (PKBM), and Women's Empowerment Organizations. The analysis focuses on face-to-face dialogue, commitment to the process, and the outcomes achieved through the implementation of the program in Bone Regency. This study employed a qualitative descriptive research method to provide an objective description and explanation of the actual roles of the Regional Development Planning Agency, the Department of Education, the Department of Women's Empowerment and Child Protection, Community Learning Activity Centers, and Women's Empowerment Organizations in fulfilling children's right to education and addressing the issue of out-of-school children through the Gemar Limas Program. The results of the study indicate that face-to-face dialogue led by the Regional Development Planning Agency plays a crucial role in ensuring that each institution performs its responsibilities in accordance with the Regional Action Plan (RAD) and establishes specific targets during coordination meetings. Commitment to the process demonstrated by each institution is based on the principle of “No One Left Behind,” ensuring that children's participation is continuously supported throughout the program implementation. The outcomes achieved show that more than 39,000 children were involved in the program between 2017 and 2023. The program also received recognition as one of the Top 99 Public Service Innovation (KIPP) nominees for its innovative contribution and has been adopted at both provincial and national levels.